2006
DOI: 10.1074/jbc.m603473200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of X/Y Linker Region and N-terminal EF-hand Domain in Nuclear Translocation and Ca2+ Oscillation-inducing Activities of Phospholipase Cζ, a Mammalian Egg-activating Factor

Abstract: Sperm-specific phospholipase C-zeta (PLC) causes intracellular Ca2؉ oscillations and thereby egg activation and is accumulated into the formed pronucleus (PN) when expressed in mouse eggs by injection of cRNA encoding PLC, which consists of four EF-hand domains (EF1-EF4) in the N terminus, X and Y catalytic domains, and C-terminal C2 domain. Those in the N terminus of EF1. Ca 2؉ oscillation-inducing activity was lost by the former mutation and was remarkably inhibited by the latter. A short sequence 374 -383… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
85
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 43 publications
2
85
0
Order By: Relevance
“…It has been reported that an RNA concentration of at least 0.5 mg/ml is required for s-PLCζ to induce Ca 2+ oscillations, whereas an RNA concentration of 0.001-0.002 mg/ml is enough for PLCζ to induce Ca 2+ oscillations [16,26]. In the case of s-PLCζ, small Ca 2+ oscillations begin later than when using PLCζ and they are followed by discrete small Ca 2+ spikes [24,26]. Coinciding with these reports, we found that resumption of meiosis as well as pronuclear formation was delayed in s-PLCζ RNA (1 mg/ml)-injected eggs compared with eggs injected with PLCζ RNA (0.002 mg/ml; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that an RNA concentration of at least 0.5 mg/ml is required for s-PLCζ to induce Ca 2+ oscillations, whereas an RNA concentration of 0.001-0.002 mg/ml is enough for PLCζ to induce Ca 2+ oscillations [16,26]. In the case of s-PLCζ, small Ca 2+ oscillations begin later than when using PLCζ and they are followed by discrete small Ca 2+ spikes [24,26]. Coinciding with these reports, we found that resumption of meiosis as well as pronuclear formation was delayed in s-PLCζ RNA (1 mg/ml)-injected eggs compared with eggs injected with PLCζ RNA (0.002 mg/ml; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The Ca 2+ oscillation-inducing activity is lost by immunodepletion of PLCζ in sperm extracts [16], and transgenic RNA interference of PLCζ results in a low rate of egg activation [22]. Moreover, PLCζ containing the consensus nuclear localization signal between the X and Y domains accumulates in the pronuclei [23][24][25][26], which is consistent with the Ca 2+ oscillation-inducing activity derived from sperm being localized in the pronuclei of fertilized eggs [7,27,28]. It is thus likely that PLCζ acts as the sperm factor that triggers the Ca 2+ oscillations required for egg activation.…”
mentioning
confidence: 99%
“…Furthermore, EF-hand domains seem also to play a role in nuclear translocation (Kouchi et al, , 2005Yoda et al 2004). According to Kuroda et al (2006), Trp13, Phe14, and Val18, which may be necessary for appropriate conformation for nuclear translocation, may also be necessary to keep normal Ca 2+ oscillationinducing activity as well. Nevertheless, despite the lack of a part of the N-terminal of all teleosts studied so far, at least some of these Plcζs still can trigger Ca 2+ oscillations.…”
Section: Molecular Structure and Functionmentioning
confidence: 99%
“…In teleost species, studies showed that a deletion of a part of the EF-hand domain reduces the Ca 2+ oscillatory activity of Plcζ (Kouchi et al, 2005;Kuroda et al, 2006). It remains possible that eel Plcζ1 does not trigger Ca 2+ oscillation, however medaka Plcζ, which is similarly truncated at its N-terminus, can induce Ca 2+ oscillation in mouse oocytes but at a lower activity than for fulllength mammalian PLCζ (Coward et al, 2011;Kuroda et al, 2006;Ito et al, 2008). These results suggest that these domains are involved in the Ca 2+ signal but are not obligatory to induce Ca 2+ oscillation.…”
Section: Molecular Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation